Species Determined Peculiarities of the Tick-Man Contacts in the South of the Primorsky Territory - T. V. Zvereva; A. V. Allenov; A. Ya. Nikitin (Проблемы особо опасных инфекций, 2015)
Ticks’ ability to attack man (aggressiveness) is an important characteristic impacting the ticks’ epidemiological role. Objective of the study is to assess the aggressiveness of the ticks inhabiting the south of the Primorsky Territory. It is based on the materials collected in the territory of Partizansky Region in 2012-2013. Ticks’ aggressiveness toward man has been defined by comparing the species’ community structure when collecting imago specimens on a cloth from plants (3,944 specimens are examined) and when removing ticks from people (437). In total, five species are identified: Ixodes persulcatus , Haemaphysalis concinna , H. japonica douglasi, Dermacentor silvarum (being dominant species), and I. pavlovskyi (which is rarely found in Partizansky Region) . Cases of tick attacks have been registered during April through October and November: this period being the peak of activity in I. persulcatus , and activity decay in H. concinna. The percentage of I. persulcatus against the total number of ticks, removed from people, has amounted to 86.3 %; the percentage of the same species collected from plants has amounted to 44.9 %. This is maximum index of aggressiveness. I. pavlovskyi also shows high level of aggressiveness, but as it is of rare occurrence it does not have any epidemiological weight in Partizansky Region. H. japonica attacks more often than H. concinna. In order to assess the difference in the epidemiological significance of these two species individual infection rate should be studied. As for D. silvarum, the percentage of this species removed from people is lower than that collected from plants, thus currently the epidemiological significance of this species in the south of Primorsky Territory is relatively low.